2017
DOI: 10.1002/cb.1636
|View full text |Cite
|
Sign up to set email alerts
|

The role of negative publicity in consumer evaluations of sports stars and their sponsors

Abstract: This paper aims to specify and test empirically the impact that two types of negative information (immorality and incompetence) about a sports star have on consumers' perceptions of the sports star and the sponsor. The moderating role of game relevance (game-related and non-game-related) and fan identification with a sports star (high identification and low identification) are also investigated. Using a sample of South Korean consumers (n = 249), we found in the experiment that the type of negative information… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 63 publications
0
24
0
Order By: Relevance
“…The study of choice tries to explain all the factors that affect consumers' real choices. The search to identify factors that affect choice has taken researches to study a wide variety of aspects, such as the effects of dynamic sensorimotor experiences (Kwon & Adaval, 2013); the value of mistakes in product choice (Reich, Kupor, Smith, Dahl, & Hoegg, 2018); the effect of advertising metaphors on choice and the moderating role of goal orientation in choice decisions (Kao, Zhang, Yu, & Wu, 2017); the role of negative publicity in consumer evaluations of sports stars and their sponsors (Yoon & Shin, 2017), or switching behavior as a function of the number of options available (Sharma & Nair, 2017).…”
Section: Positivist Consumer Behavior Researchmentioning
confidence: 99%
“…The study of choice tries to explain all the factors that affect consumers' real choices. The search to identify factors that affect choice has taken researches to study a wide variety of aspects, such as the effects of dynamic sensorimotor experiences (Kwon & Adaval, 2013); the value of mistakes in product choice (Reich, Kupor, Smith, Dahl, & Hoegg, 2018); the effect of advertising metaphors on choice and the moderating role of goal orientation in choice decisions (Kao, Zhang, Yu, & Wu, 2017); the role of negative publicity in consumer evaluations of sports stars and their sponsors (Yoon & Shin, 2017), or switching behavior as a function of the number of options available (Sharma & Nair, 2017).…”
Section: Positivist Consumer Behavior Researchmentioning
confidence: 99%
“…Because of that, many of the current studies concentrate on the effects of several types of negative information (e.g. immorality vs incompetence; intended vs unintended misconduct) on consumers’ attitudes toward the sponsored property, as well as the sponsor brand (Um, 2013; Sato et al , 2015; Yoon and Shin, 2017). For instance, Um (2013), as well as Sato et al (2015), empirically showed that negative information about a sponsored athlete caused by an intended misbehavior leads to stronger negative consumer attitudes toward the sport entity involved compared to an unintended wrongdoing.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Adolescents and body cult: the influence of Internet advertising in search of the idealized male body ISSN: 1696-019X / e-ISSN: 2386-3978 perceptions and behaviours by which men and women are governed and adopt as natural and logical (Aranceta & Serra, 2006;Yoon & Shin, 2017). Body reality has become and expressive symbol of the individuals´ positioning within society.…”
Section: July-december Of 2019mentioning
confidence: 99%
“…Advertising feeds on metaphorical constructions about sexuality and the body that have been consensual and socially stereotyped. The advertisements and, above all, for beauty and aesthetics products now present a human body drowned by a metaphorical and commercial figuration of perfection and happiness; a perfection symbolized through slender and slim catwalk models, and depilated and sculptural muscular men (Yoon & Shin, 2017;Pérez Gauli, 2000).…”
Section: July-december Of 2019mentioning
confidence: 99%